2018
DOI: 10.1051/matecconf/201815603012
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Oxidation Processes (AOPs) for Refinery Wastewater Treatment Contains High Phenol Concentration

Abstract: Abstract. Petroleum Refinery wastewater is characterized by a high phenol content. Phenol is toxic and resistant to biological processes for treatment of the petroleum refinery wastewater. The combination of an AOP and a biological process can be used for treatment of the refinery wastewater. It is necessary to conduct a study to determine the appropriate condition of AOP to meet the phenol removal level. Two AOP configurations were investigated: H2O2 / UV and H2O2 / UV / O3. From each process samples, COD, ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Wang et al [148] also reported that AOPs are usually rapid processes with high treatment efficiencies and little residual production, but on the other hand, associated with high energy requirements. Azizah and Widiasa [149] investigated the application of H 2 O 2 /UV and H 2 O 2 /UV/O 3 configurations for the treatment of PRWW with high phenol concentrations. High phenol degradation of about 93.75% was achieved using a H 2 O 2 /UV/O 3 configuration with 1000 ppm of H 2 O 2 after 120 min.…”
Section: Advanced Oxidation Processesmentioning
confidence: 99%
“…Wang et al [148] also reported that AOPs are usually rapid processes with high treatment efficiencies and little residual production, but on the other hand, associated with high energy requirements. Azizah and Widiasa [149] investigated the application of H 2 O 2 /UV and H 2 O 2 /UV/O 3 configurations for the treatment of PRWW with high phenol concentrations. High phenol degradation of about 93.75% was achieved using a H 2 O 2 /UV/O 3 configuration with 1000 ppm of H 2 O 2 after 120 min.…”
Section: Advanced Oxidation Processesmentioning
confidence: 99%